PENGARUH PEMBERIAN BIOCHAR TANDAN KOSONG KELAPA SAWIT DAN MIKORIZA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays sacharrata L.) DI TANAH ULTISOL - Atria Deamalda Tarigan; Nelvia Nelvia (Jurnal Agroekoteknologi, 2020)
The main problems of sweet corn cultivation in Ultisol medium are sour reactions, Al saturation and height P fixation, as well as low availability macro, micro nutrients especially Mo and Si. The provision of empty oil palm biochar is able to increase the growth and yield of sweet corn crops because the Biochar TKKS contains macro and micro nutrients such as N, P, K, Ca and Mg and also as a useful soil material to improve physical, chemical and biological properties of soil to increase pH, C-Organic, Ca, K, Mn, P, and mycorrhiza application be able to increase the availability of P so the fixation of P can be suppressed. The purpose of this research to learn the main influences of the Biochar TKKS, the main influence of mycorrhiza and the interaction of the growth and yield of sweet corn in the Ultisol medium. The experiment was conducted in the Experimental farm of the Agriculture Faculty, the University of Riau from May to August 2019.Research of experiments in the form of 4×3 factorial using Complete RandomDesign. The Biochar TKKS consists of four levels (0, 25, 3.75, 50 g polibag-1) asthe first factor, mycorrhiza consists of three levels (0, 10, 15 g plant-1) as thesecond, each repeated three times. The results of the study show that giving of the biochar TKKS dose 3.75 g polibag-1 and mycorrhiza dose 15 g plant-1 in theUltisol medium increased on plant height, straw weight, cob length and number of rows of each cob compared to no treatment.